1996
DOI: 10.1007/bf00242908
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hippocampal cell discharge patterns and theta rhythm spectral properties as a function of walking velocity in the guinea pig

Abstract: Dorsal hippocampal theta rhythm (theta) and extracellular unit activity from CA1 pyramidal layer were recorded in awake guinea pigs, both during standing and during walking on a conveyor belt at increasing speeds. Amplitude, frequency and rhythmicity of theta increased linearly with the movement speed. In this preparation we found the same three types of unit discharge patterns that have been described in anesthetized rats in the presence of spontaneous or induced hippocampal theta: type 1, rhythmic at theta f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 18 publications
5
86
1
Order By: Relevance
“…Burgess et al (2005Burgess et al ( , 2007 introduced an "oscillatory interference" theory, hypothesizing that theta oscillations are generated by velocity-controlled oscillators (VCOs), which perform path integration by modulating their frequencies in proportion with the speed and direction of a rat's translational movements. Supporting this idea, theta frequency is indeed modulated by a rat's movement speed (Rivas et al, 1996;Geisler et al, 2007), and oscillatory properties of spatial neurons are correlated with their spatial tuning parameters in accordance with predictions of oscillatory interference models (Burgess et al, 2007;Giocomo et al, 2007;Jeewajee et al, 2008a;Zilli et al, 2009). However, oscillatory interference models explicitly require that VCO frequencies vary as the cosine of an animal's movement direction, and such directional modulation of theta oscillations has never been observed.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Burgess et al (2005Burgess et al ( , 2007 introduced an "oscillatory interference" theory, hypothesizing that theta oscillations are generated by velocity-controlled oscillators (VCOs), which perform path integration by modulating their frequencies in proportion with the speed and direction of a rat's translational movements. Supporting this idea, theta frequency is indeed modulated by a rat's movement speed (Rivas et al, 1996;Geisler et al, 2007), and oscillatory properties of spatial neurons are correlated with their spatial tuning parameters in accordance with predictions of oscillatory interference models (Burgess et al, 2007;Giocomo et al, 2007;Jeewajee et al, 2008a;Zilli et al, 2009). However, oscillatory interference models explicitly require that VCO frequencies vary as the cosine of an animal's movement direction, and such directional modulation of theta oscillations has never been observed.…”
Section: Introductionsupporting
confidence: 69%
“…Averaged across all directions, these opposing influences should cancel each other out, yielding a prediction that the mean VCO frequency would be identical for all running speeds. Contradicting this prediction, prior studies have shown that the theta frequency increases with running speed when movement direction is disregarded (Rivas et al, 1996;Geisler et al, 2007;Jeewajee et al, 2008a). One simple way to account for these results is to assume that the VCO base frequency [Eq.…”
Section: Modulation Of Burst Frequencies By Running Speedmentioning
confidence: 99%
“…The model is supported by data showing that running speed influences the frequency of theta rhythm (Whishaw and Vanderwolf 1973;Rivas et al 1996;Slawinska and Kasicki 1998;Maurer et al 2005). The modulation of entorhinal frequency (or distal dendritic frequency) by running speed s should alter the frequency of current sinks in stratum lacunosum-moleculare of region CA1 (Brankack et al 1993).…”
Section: Simulation Of Interfering Oscillatory Activitymentioning
confidence: 75%
“…3A). However, because it has been reported (27)(28)(29)(30) that the frequency of the exploratory theta oscillations increases with the speed of the animal, we investigated whether or not this occurred in our mice. Because of the limitations of conventional power spectra in terms of time/ frequency resolution, we calculated the Wavelet power spectrum (31) as a function of time ( Fig.…”
Section: Exploratory Theta Oscillations In Wild-type and Task-3 Ko Anmentioning
confidence: 99%